Faktor-Faktor Yang Mempengaruhi Penggunaan Gadget Pada Psikis Anak Usia Dini - Assyifa, Alya; Syahputri, Bilqis; Nadila, Nadila (Journal of Sustainable Education, 2025)
In today's modern era, technological development has progressed rapidly to facilitate various human activities. A wide range of technologies can now be easily found, one of the most popular being gadgets. Gadgets are small-sized electronic devices designed with specific functions and ease of use, capable of delivering technological innovations that enhance efficiency in daily life. Thus, gadgets can be considered a form of technological advancement. However, it cannot be ignored that gadget use also brings both positive and negative impacts, especially for young children. This study aims to examine the extent of the influence of gadgets on the psychological development of early childhood. Considering that gadgets can be accessed by anyone and used for various purposes depending on the owner's needs, the role of parents becomes crucial in supervising and limiting gadget use among children, particularly at vulnerable ages such as early childhood.